Trade linkages and skill demand : empirical evidence for the Malaysian electrical and electronics industries - Azmafazilah Jauhari,; Noor Aini Khalifah, (Penerbit Universiti Kebangsaan Malaysia, 2018)
This article empirically investigates whether trade linkages have any contribution to skill upgrading in the Malaysian electrical and electronics (E&E) firms by using establishment level data. The richness of data provided by Department of Statistics Malaysia (DOSM) enable us to explore the direct impact of each aspect of trade linkages, including exports of goods, imported inputs (outsourcing), and foreign ownership (FDI). More crucially, this research analyse the effects of the modern trade pattern, i.e. vertical trade which would best capture the current trend in the Malaysian E&E sector – high overlap in exports and imported inputs. The skill demand is analysed using dynamic skill share demand equation and GMM (generalised method of moments) estimator addresses both the endogeneity and firm fixed effect. Contrary to previous studies, results suggest that export and outsourcing do not significantly contribute to skill upgrading in Malaysian E&E establishments within the period under study. Plus, vertical trade and foreign share have significant negative impact on relative demand for skilled workers. These findings provide evidence that vertical trade as well as the presence of multinational corporations (MNCs) are associated with skill downgrading in Malaysian E&E sector. Empirical evidence does not uphold the conventional wisdom of the beneficial effects of trade especially ultra-vertical or export processing trade on skill upgrading.